Potentiated Osteoinductivity via Cotransfection with BMP-2 and VEGF Genes in Microencapsulated C2C12 Cells. (16th September 2015) - Shen, Yang; Qiao, Han; Fan, Qiming; Zhang, Shuhong; Tang, Tingting
Abstract : Microcapsules with entrapped cells hold great promise for repairing bone defects. Unfortunately, the osteoinductivity of microcapsules has been restricted by many factors, among which the deficiency of functional proteins is a significant priority. We potentiated the osteoinductivity of microencapsulated cells via cotransfection with BMP-2 and VEGF genes. Various tissue-derived mesenchymal stem cells and cell lines were compared for BMP-2 and VEGF cotransfection. Ethidium bromide (EB)/Calcein AM staining revealed that all of the cell categories could survive for 4 weeks after microencapsulation. An ELISA assay indicated that all microencapsulated BMP-2 or VEGF transfected cells could secrete gene products constitutively for 1 month. Particularly, the recombinant microencapsulated C2C12 cells released the most desirable level of BMP-2 and VEGF. Further experiments demonstrated that microencapsulated BMP-2 and VEGF cotransfected C2C12 cells generated both BMP-2 and VEGF for 4 weeks. Additionally, the cotransfection of BMP-2 and VEGF in microencapsulated C2C12 cells showed a stronger osteogenic induction against BMSCs than individual BMP-2-transfected microencapsulated C2C12 cells. These results demonstrated that the cotransfection of BMP-2 and VEGF into microencapsulated C2C12 cells is of potent utility for the potentiation of bone regeneration, which would provide a promising clinical strategy for cellular therapy in bone defects.